THE EFFECT OF CONFIDENCE ON ENGLISH SPEAKING SKILLS DURING CLASSROOM PRESENTATION - marla maria ignasia nahak (CV Grasta Glory, 2025)
Finding out how students' self-confidence impacts their ability to communicate in English during class presentations is the aim of this study. Despite the fact that speaking is an extremely vital ability, many students struggle to communicate properly because they lack confidence. This study employed a quantitative correlational design with 19 sixth semester students from PGRI Silampari University's English Education Study Program. A ten-item Likert scale questionnaire about speaking abilities and self-confidence was used to gather data, and it was distributed via Google Forms. The average scores for speaking abilities and self-confidence were 3.35 and 3.32, respectively, indicating a modest level. The correlation coefficient (r=0.51) indicates a moderately positive relationship between speaking abilities and self-confidence. This suggests that more confident students typically talk more effectively in class. We may conclude that students' speaking performance is significantly impacted by their level of self-confidence. By providing additional speaking practice and fostering a positive learning atmosphere, teachers can help students gain confidence.